2016
DOI: 10.3389/fpsyg.2016.00850
|View full text |Cite
|
Sign up to set email alerts
|

Anxiolytic Treatment Impairs Helping Behavior in Rats

Abstract: Despite decades of research with humans, the biological mechanisms that motivate an individual to help others remain poorly understood. In order to investigate the roots of pro-sociality in mammals, we established the helping behavior test, a paradigm in which rats are faced with a conspecific trapped in a restrainer that can only be opened from the outside. Over the course of repeated test sessions, rats exposed to a trapped cagemate learn to open the door to the restrainer, thereby helping the trapped rat to… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
57
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 30 publications
5
57
0
1
Order By: Relevance
“…In conclusion, there are multiple factors involved in the motivation to the opening behavior in the protocol proposed by Ben-Ami Bartal et al (2011) and used in the present study. This outcome is relevant as there is an increasing number of studies that used the original or modified versions of the releasing task with the purpose of studying empathy or prosocial behavior in rodents ( Ben-Ami Bartal et al, 2014 , 2016 ; Silberberg et al, 2014 ; Hachiga et al, 2018 ; Kandis et al, 2018 ; Karakilic et al, 2018 ; Fontes-Dutra et al, 2019 ; Yamagishi et al, 2019 ). Our study provided data that ruled out the desire for social contact or the exploration of the restraint box as key motivators, at least under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…In conclusion, there are multiple factors involved in the motivation to the opening behavior in the protocol proposed by Ben-Ami Bartal et al (2011) and used in the present study. This outcome is relevant as there is an increasing number of studies that used the original or modified versions of the releasing task with the purpose of studying empathy or prosocial behavior in rodents ( Ben-Ami Bartal et al, 2014 , 2016 ; Silberberg et al, 2014 ; Hachiga et al, 2018 ; Kandis et al, 2018 ; Karakilic et al, 2018 ; Fontes-Dutra et al, 2019 ; Yamagishi et al, 2019 ). Our study provided data that ruled out the desire for social contact or the exploration of the restraint box as key motivators, at least under our experimental conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, free rats made more alarm calls when their cage-mate was restrained than when the apparatus was empty or contained a toy rat [45]. In addition, anxiolytic treatment impaired rescue behavior in rats indicating that this behavior was motivated by an affective state of anxiety elicited by the distress of the trapped conspecific [33].…”
Section: Comparisons To Ratsmentioning
confidence: 98%
“…Prosocial helping paradigms have typically employed an 'out-of-reach task' in which potential donor individuals can choose to retrieve and transfer an item to a recipient individual, for whom this item is otherwise out of reach (e.g., [32]). The current study adopted an alternative test for helping that has been used to successfully demonstrate prosocial rescue behavior in rats [33] and ants [8]. In this paradigm, a potential rescuer is free to move about a testing arena while a conspecific in the same arena is either trapped inside a restrainer apparatus that can only be opened from the outside (rats), or partially buried in sand and tied down by a nylon thread (ants).…”
Section: Introductionmentioning
confidence: 99%
“…Intranasal oxytocin was shown to improve empathy in PTSD patients (106). Ben-Ami Bartal et al showed that administration of a benzodiazepine (midazolam) impaired helping behavior in rats (107). Benzodiazepines are known to downregulate oxytocin transmission, which is linked to empathy, and reducing anxiety is also linked to deactivating HPA axis and sympathetic system.…”
Section: Empathy and Animal Models Of Psychiatric Disordersmentioning
confidence: 99%